O sistema Cooperativo como acesso à Justiça diante das demandas familiares: análise dos métodos adequados de solução de conflitos no Centro de Conciliação e Mediação de família, no fórum Desembargador Sarney Costa - MENDES, Dyhelle Christina Campos (2023)
The search for effectiveness in access to justice runs through to the multiport justice system. Thus, before this fundamental right, it is important to observe the principle of adequacy in order to understand that there are several ways of solving dissents. In this respect, the appropriate means of conflict resolution, such as conciliation and mediation are included as dispute resolution mechanisms, aiming at social pacification. The current Federal Constitution, the CNJ Resolution n. 125/2010, the Code of Civil Procedure and the Mediation Law comprise the Brazilian cooperative system in favor of encouraging self-compositive means as a form of access to justice, highlighting mediation and conciliation. From this, the following problem arises to be answered in this academic production: to what extent does the application of appropriate methods of conflict resolution reflect the improvement of access to justice? For this, I took as a basis the Center for Conciliation and Family Mediation, located in Sarney Costa Judge Forum, to analyze this pointed question. Thus, as a general objective, it was aimed to analyze to what extent the use of appropriate methods of conflict resolution in the Center for Conciliation and Family Mediation, between the years 2017 to 2021, improved access to justice. In relation to the specific objectives, it works with: to undertake a re-reading of access to justice through to cooperative system; to analyze the application of appropriate methods of conflict resolution as a form of access to justice; and compare the use of appropriate methods of conflict resolution before the Center for Conciliation and Family Mediation, between 2017 and 2021. About the chosen methodology, the method of approach was the deductive, procedural, legal- comparative and the techniques of research were bibliographical, documentary, field research, also making up the qualitative and quantitative researches. Finally, it was concluded that there was an improvement in access to justice through application of conciliation and mediation, with the broader understanding of the theme for the search for access to the just legal order, with pleading for constitutional guarantees.